Have thyroid hormones an impact on ovarian cancer? - Klaudia Żak; Sylwiusz Niedobylski; Milena Leziak; Karolina Maliszewska; Mirella Czapska; Katarzyna Skórzyńska-Dziduszko (Kazimierz Wielki University, 2018)
Thyroid hormones show not only genomic, but also nongenomic activity, which is related to specific membrane, cytoplasmic and organelle receptors. The best known receptors are located on the alpha-V-beta-3 integrin of cell membrane. Their stimulation results in an activation of mitogen-activated protein kinases (MAPKs) or phosphoinositide 3-kinase (PI3K), which directly leads to an inhibition of apoptosis and increased proliferation of tumor cells, as well as promotes angiogenesis and metastasis formation. In ovarian cancer cells L-thyroxine is proven to be involved in MAPK activation as well as in the up-regulation of expression and enhanced cellular accumulation of programmed death ligand 1 (PD-L1), which results in an inhibition of neoplastic cells apoptosis.